CREATING HIGH PERFORMANCE TEAMS : APPLIED STRATEGIES AND TOOLS FOR MANAGERS AND TEAM MEMBERS - Aldag, Ramon J, 1945-
Creating High Performance Teams is an accessible and thorough new introduction to this key area of business education. Written by teams experts Ray Aldag and Loren Kuzuhara, this book provides students with both a firm grounding in the key concepts of t